Kontribusi orang tua dan guru dalam pembentukan sikap mandiri anak usia dini - PALUPI, ANNISA DIA (Maliki Interdisciplinary Journal, 2026)
The development and instillation of an independent character are essential from an early age. Teachers and parents play a crucial role in providing appropriate roles so that children can perform various activities independently according to their developmental stage. This discussion aims to describe the roles of teachers and parents in fostering independence in early childhood in early childhood education settings, as well as the supporting and inhibiting factors encountered in its implementation. The discussion results indicate that teachers act as facilitators, motivators, guides, and role models through child-centered learning and the habituation of independent behavior in routine activities. Adequate support facilities, a conducive learning environment, and good cooperation between teachers and parents are supporting factors in developing children’s independence. Meanwhile, excessive assistance from adults and a lack of opportunities for children to practice independence are inhibiting factors. Thus, ongoing efforts are needed from teachers, parents, and early childhood education institutions to strengthen the stimulation of children’s independence optimally.